2020
DOI: 10.1200/jco.2020.38.6_suppl.618
|View full text |Cite
|
Sign up to set email alerts
|

NIVOREN GETUG-AFU 26 translational study: Association of PD-1, AXL, and PBRM-1 with outcomes in patients (pts) with metastatic clear cell renal cell carcinoma (mccRCC) treated with nivolumab (N).

Abstract: 618 Background: The NIVOREN GETUG-AFU 26 study reported safety and efficacy of N in mccRCC pts in a “real world setting”. A translationnal research program was launched to characterize immune cell populations in the tumor by immunohistochemistry (IHC) and correlate them with outcome on N. Methods: All pts treated with N in the GETUG AFU 26 NIVOREN trial who consented for translational program and with available archived paraffin- embedded (FFPE) tumor tissue samples were eligible. Tumor were centrally reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Macrophage reprogramming is another promising approach nowadays, as diverse therapeutic strategies have been suggested to suppress tumor-associated macrophage recruitment, switching them back to the antitumor M1 phenotype [ 121 ]. Nevertheless, several studies have reported that high M2 macrophage tumor infiltration is associated with a more durable response to anti-PD-1 therapy [ 116 , 168 ]. This association was not found in patients treated with TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage reprogramming is another promising approach nowadays, as diverse therapeutic strategies have been suggested to suppress tumor-associated macrophage recruitment, switching them back to the antitumor M1 phenotype [ 121 ]. Nevertheless, several studies have reported that high M2 macrophage tumor infiltration is associated with a more durable response to anti-PD-1 therapy [ 116 , 168 ]. This association was not found in patients treated with TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating only the second-and later lines of treatment were those reported by Dizman et al [30] and Vano et al [29]. All other articles included patients in the first-line, second-line or beyond.…”
Section: Discussionmentioning
confidence: 99%
“…In only 3 studies (Braun et al [26,27] and Vano et al [29]) and in the primary cohort of Miao et al, patients received nivolumab as a single therapy. In the validation cohort of the study by Miao et al and in all others, the therapies were as follows: antiPD1/ L1 + anti-CTLA-4, anti-PD1/L1 + anti-VEGF-TKI, anti-PD1/L1 + another drug or anti-CTLA-4 alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study from an institutional cohort of patients at MSKCC (n = 105) that included 24% patients with BAP1 mutations showed a shorter time to treatment failure for patients with mutated BAP1 in response to VEGF-TKIs (median 6.4 months vs 11.0 months; p = 0.01) as well as a shorter overall survival (median 28.7 months vs. not reached; p = 0.02)[53].iii) Response to immunotherapy-based therapy:Even though data from larger clinical trials using immune checkpoint inhibitors is lacking, smaller studies have tried to dissect this relationship. The NIVOREN GETUG-AFU 26 study included 324 patients who had received the programmed death-1 (PD-1) inhibitor nivolumab[54]. The investigators reported no association of BAP-1 loss with PFS or OS (p = 0.6 and 0.9 respectively).…”
mentioning
confidence: 99%